Decoding Leadership Pedagogy in Lutung Kasarung: A Semiotic Analysis of Constitutionalism and Religious Moderation - M. Mujib Hidayat; Muhammad Hafizh; Roshifah Jauhari; Dini Pepilina (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
The crisis of leadership in Indonesia is marked by a weakening of moral integrity, the dominance of elite interests, low democratic accountability, social polarization, and the challenge of managing diversity. Although the study of religious leadership and moderation has advanced, the integration of Sundanese local wisdom with the moderate leadership paradigm remains limited. This research aims to analyze the symbolic meaning of the Lutung Kasarung legend and to formulate an authentic leadership framework relevant to religious moderation. The research uses a qualitative approach based on literature studies with the main source of Ajip Rosidi's work (2023) and literature from the last decade. The data were analyzed descriptively through Roland Barthes' mythological semiotics. The results show that Kamandaka figures embody integrity, justice, humility, empathy, deliberation, and collective responsibility, which align with the principles of religious moderation: tawassuṭ, tawāzun, tasāmuḥ, and i'tidāl. The novelty of the research lies in integrating semiotics, local wisdom, constitutional values, and religious moderation into a contextual leadership pedagogy. These findings confirm that local narratives can be an alternative learning resource to strengthen inclusive leadership in Islamic education.